ycobiotic inventory of the region of Tapalpa, Jalisco, Mexico - Gándara, Etelvina; Guzmán Dávalos, Laura; Guzmán, Gastón; Rodríguez, Olivia (Instituto de Ecología, A.C., 2014)
A list of 233 taxa (species and varieties) of fungi (229 macromycetes and four micromycetes) from Tapalpa region, State of Jalisco (Mexico) is presented. The studied material was collected from 2000 to 2003, mainly in Pinus and Quercus forests. Additional specimens from the IBUG herbarium gathered in this region were also studied. Twenty-one taxa are first records from Jalisco State. In the studied fungi, 205 (88%) species belong to Basidiomycota, 22 (9.5%) to Ascomycota, and 6 (2.5%) to Myxomycota. This is the first mycological inventory of the area.